Answer:
a. 4r² b. 2r c. 6 cm
Step-by-step explanation:
The surface area A of the cube is A = 24r². We know that the surface area, A of a cube also equals A = 6L² where L is the length of its side.
Now, equating both expressions, 6L² = 24r²
dividing both sides by 6, we have
6L²/6 = 24r²/6
L² = 4r². Since the area of one face is L², the polynomial that determines the area of one face is A' = 4r².
b. Since L² = 4r² the rea of one face of the cube, taking square roots of both sides, we have
√L² = √4r²
L = 2r
So, the polynomial that represents the length of an edge of the cube is L = 2r
c. The length of an edge of the cube is L = 2r. When r = 3 cm.
L = 2r = 2 × 3 cm = 6 cm
So, the length of an edge of the cube is 6 cm.
Answer: C
Step-by-step explanation:
Simplify the expression to 2^1/4
Now transform the expression using a^m/n = n root a raised to a power of m.
And that's how you get your answer.
Answer:
No its not
Step-by-step explanation:
When 42(x + 14y) is simplified:
42(x + 14y)
Expand and remove the brackets. Remember brackets mean to multiply.
42*x
42x
42*14y
588y
42x+588y
Therefore 42x-56 is NOT EQUIVALENT to 42(x + 14y) but is equivalent to 42+588y
No solution
because delta ( b^2 - 4ac ) is lower than 0(zero) .
1. -3/2
2. 2
3. 1/2
4.0
5. 1/2
6. -3/4
7. -1/4
8. -8/11
9. 0
10. -1/5